Difficulties in the treatment of infective endocarditis of unknown aetiology complicated by haemorrhagic stroke, cerebellum stroke, and spleen abscesses - Kraśnicka-Sokół, Beata P.; Brodowski, Karol; Kanafa, Krzysztof; Filczak, Krzysztof; Laskowski, Stanisław; Kochmański, Marek (Medical Studies/Studia Medyczne, 2016)
A 59-year-old man was admitted to the Rheumatology Department in order to conduct diagnostics of a hypoechogenic lesion located in the lower pole of the spleen. After 17 days of hospitalisation at the Department of Rheumatology and the Department of Neurology, the patient was referred to the Internal Medicine Ward due to a suspicion of advanced infective endocarditis. Seven days of antibiotic and antifungal therapy resulted in a reduction of C-reactive protein levels from 133.38 mg/l to 29.78 mg/l. Control echocardiography did not show progression of bacterial vegetation, but revealed an increase in the severity of bicuspid valve regurgitation. Following pharmacotherapy, on the 23rd day of hospitalisation the patient was transferred to the Department of Cardiosurgery and Transplantology at the Institute of Cardiology for urgent surgical treatment. After successful surgery the patient underwent physiotherapy, resulting in partial resolution of neurological symptoms. Currently, 2 years after the event, the patient remains in good general state. We therefore conclude that the IE Risk Index is of high clinical value.